1996
DOI: 10.1055/s-0038-1650612
|View full text |Cite
|
Sign up to set email alerts
|

A Heparin Cofactor II Mutation (HCII Rimini) Combined with Factor V Leiden or Type I Protein C Deficiency in Two Unrelated Thrombophilic Subjects

Abstract: Summary305 patients with juvenile thromboembolic episodes were screened for the presence of heparin cofactor II deficiency. The heterozygous deletion of two bases was found in the exon 5 of the heparin cofactor II gene in two unrelated patients, very likely due to a founder effect. This molecular lesion, causing a frameshift and elongated translation, affects the core of the molecule and should cause the complete unfolding of the protein, which is in accordance with the observed type I deficiency. The correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…This postulate is supported by additional reports that characterize the involvement of other genes. For example, co-heterozygosity for heparin cofactor II ( SERPIND1 ) and factor V Leiden or protein C deficiency was observed in subjects who experienced juvenile thromboembolic episodes (Bernardi et al 1996), as well as in other families with thrombosis tested for these variants (Lane et al 1996; Sansores-Garcia and Majluf-Cruz 1998). Two sisters in one family study were found to be homozygous for a factor XII deficiency-associated mutation ( F12 ) and heterozygous for factor V Leiden; one sister exhibited multiple thrombotic events, whereas the other was asymptomatic (Girolami et al 2010) suggesting that there is significantly greater complexity underlying disease predisposition than just the presence of two or three variants.…”
Section: Discussionmentioning
confidence: 99%
“…This postulate is supported by additional reports that characterize the involvement of other genes. For example, co-heterozygosity for heparin cofactor II ( SERPIND1 ) and factor V Leiden or protein C deficiency was observed in subjects who experienced juvenile thromboembolic episodes (Bernardi et al 1996), as well as in other families with thrombosis tested for these variants (Lane et al 1996; Sansores-Garcia and Majluf-Cruz 1998). Two sisters in one family study were found to be homozygous for a factor XII deficiency-associated mutation ( F12 ) and heterozygous for factor V Leiden; one sister exhibited multiple thrombotic events, whereas the other was asymptomatic (Girolami et al 2010) suggesting that there is significantly greater complexity underlying disease predisposition than just the presence of two or three variants.…”
Section: Discussionmentioning
confidence: 99%
“…A similar prothrombotic synergism has been suggested between heterozygous HCII deficiency and mild (factor V Leiden) or strong (protein C deficiency) prothrombotic genetic risk factors. 7 The murine model, however, suggests that HCII might protect against thrombosis in the arterial circulation. 21 It is of interest that 2 other deficiency variants of HCII have been associated with coronary artery disease 6 and multiple atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 2, comparison of the proband sequence with previously reported cDNA 12,13 and genomic HCII sequences [5][6][7]14 showed 6 nucleotide differences: G-181A, A36C, T5718C (Gly149), A5924G (Lys218Arg), G12809A (Glu428Lys), and T12915C (His463) (nucleotide numbering according to Herzog et al). 5 The genetic change T12915C (His463), found in heterozygous state in the proband, has been previously described as a common polymorphism.…”
Section: Genetic Characterization Of Hcii Valenciamentioning
confidence: 91%
See 1 more Smart Citation
“…One, insertion of a T in exon 2, was discovered in a Japanese patient who suffered from coronary artery disease [28]. The second mutation, a deletion of two nucleotides in exon 5, was found in two apparently unrelated Italian patients with thrombophilia [29].…”
Section: Heparin Cofactor IImentioning
confidence: 99%